2021
DOI: 10.52380/mojet.2021.9.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Among Social Media Addiction, Cognitive Absorption, and Self-Esteem

Abstract: The present study aimed at testing a model developed to uncover the relationships among social media addiction, cognitive absorption, and self-esteem. This studys’ sample consisted of 361 university students, 198 of whom were females, and 163 were males. Data were collected using the Social Media Addiction Scale (SMAS), the Cognitive Absorption Scale (CAS), and the Rosenberg Self-Esteem Scale (RSES). Structural Equation Modelling (SEM) was used to analyse the data. The results showed a positive and significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…As shown by the mediation model results, perceived stress was found to be a significant positive predictor of SN addiction, as well as of temporal dissociation. Moreover, temporal dissociation as a result of cognitive absorption was shown to predict SN addiction as well, in line with the results presented in another study where the relationship between cognitive absorption and SN addiction was analysed through structural equation modelling [66]. Thus, the results of the mediation model suggest that higher levels of perceived stress directly predict a stronger addiction to SNs, but also that, when feeling more stressed, there is an increased risk of temporal dissociation while on SNs-which, in turn, affects SN addiction.…”
Section: Discussionsupporting
confidence: 86%
“…As shown by the mediation model results, perceived stress was found to be a significant positive predictor of SN addiction, as well as of temporal dissociation. Moreover, temporal dissociation as a result of cognitive absorption was shown to predict SN addiction as well, in line with the results presented in another study where the relationship between cognitive absorption and SN addiction was analysed through structural equation modelling [66]. Thus, the results of the mediation model suggest that higher levels of perceived stress directly predict a stronger addiction to SNs, but also that, when feeling more stressed, there is an increased risk of temporal dissociation while on SNs-which, in turn, affects SN addiction.…”
Section: Discussionsupporting
confidence: 86%
“…These results indicate that self-esteem is an important protective factor, which thereby mediates the direct influence of depression on SMA, although it does not eliminate its direct effect. This is consistent with previous studies that have found a negative relationship between self-esteem and SMA [19,[41][42][43]71,72]; as self-esteem decreases, the risk of SMA increases.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous investigations [ 19 , 41 , 42 , 43 , 70 , 71 ], our results highlighted a significant negative correlation between SMA and self-esteem, which can be explained by referring to the protective role of self-esteem for addictive behaviors, as well as by the higher dependence on others for approval seen in individuals with low self-esteem. In the same vein, we can interpret data regarding the significant negative correlation between self-esteem, FoMO, and ON-FoMO that emerged in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Referencing Social Comparison Theory, Acar et al (2020) proposed the negative association between the variables betrayed a desire within low selfesteem individuals for upward social comparison (i.e., comparing oneself with superior others), wherein they might discover a better self-reflection; however, the receipt of negative feedback might diminish their already low level of self-esteem further. The negative association between self-esteem and SMD has received empirical support elsewhere, also (e.g., de Cock et al, 2014;Blachnio, Przepiorka, & Pantic, 2016;van den Eijnden, Lemmens, & Valkenburg, 2016;Andreassen, Pallesen, & Griffiths, 2017;Banyai et al, 2017;van Rooij et al, 2017;Hawi & Samaha, 2018;Hou et al, 2019;Khan, Khan, & Moin, 2021;Zeynep, 2021).…”
Section: 31mentioning
confidence: 95%
“…The present study hopes to develop the debate by factoring in a comparative linguistic dimension, which, to the best of the author's knowledge, has not been previously addressed. Considering the longitudinal association between self-esteem and SMD, the literature suggests this has yet to be fully addressed, which is an issue requiring resolution (Akkus, 2021).…”
Section: Social Media Dependency and Self-esteem: Longitudinal Perspe...mentioning
confidence: 99%